2004
DOI: 10.1038/nm1020
|View full text |Cite
|
Sign up to set email alerts
|

A new role for Nogo as a regulator of vascular remodeling

Abstract: Although Nogo-A has been identified in the central nervous system as an inhibitor of axonal regeneration, the peripheral roles of Nogo isoforms remain virtually unknown. Here, using a proteomic analysis to identify proteins enriched in caveolae and/or lipid rafts (CEM/LR), we show that Nogo-B is highly expressed in cultured endothelial and smooth muscle cells, as well as in intact blood vessels. The N terminus of Nogo-B promotes the migration of endothelial cells but inhibits the migration of vascular smooth m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
286
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(305 citation statements)
references
References 22 publications
15
286
1
Order By: Relevance
“…In addition, using mice deficient in Nogo-A or NgR, some reports have shown axonal regeneration and marked behavioral improvement following SCI Kim et al, 2003Kim et al, , 2004, whereas other studies did not detect any differences when compared to their wild-type littermates (Zheng et al, 2003(Zheng et al, , 2005. Other recent reports have suggested a more complex role for Nogo other than associated with inhibition of axonal outgrowth (Jokic et al, 2005;He et al, 2004;Karnezis et al, 2004;Acevado et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, using mice deficient in Nogo-A or NgR, some reports have shown axonal regeneration and marked behavioral improvement following SCI Kim et al, 2003Kim et al, , 2004, whereas other studies did not detect any differences when compared to their wild-type littermates (Zheng et al, 2003(Zheng et al, , 2005. Other recent reports have suggested a more complex role for Nogo other than associated with inhibition of axonal outgrowth (Jokic et al, 2005;He et al, 2004;Karnezis et al, 2004;Acevado et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…These aspects have been discussed previously 85 and reviewed recently in the context of graft pathophysiology 86 and here we bring the literature up to date with recent original papers in this area. It has recently been demonstrated that NogoB is a novel regulator of the vascular system 87 and that NogoB overexpression using the Ad5 approach significantly reduced neointima formation in pig venous grafts. 88 An interesting recently published study 89 focused on the concept that overexpression of cyclooxygenase-1 might attenuate vein graft disease.…”
Section: Studies Using Gene Therapy For Vein Graftsmentioning
confidence: 99%
“…The N terminus of Nogo has been recognized recently to have another NgR-independent action via an extreme N-terminal domain present in Nogo-B. This domain has a selective role in remodeling the vasculature after injury (Acevedo et al, 2004). Thus, Nogo appears to have multiple functional domains and receptors (supplemental Fig.…”
Section: Ngr-independent Action Of Amino-nogomentioning
confidence: 99%